The role of lateral branches on effective stiffness and local overstresses in dentin - Vennat, Elsa; Hemmati, Asef; Schmitt, Nicolas; Aubry, Denis (Journal of the mechanical behavior of biomedical materials, 2021)
The 3D microstructure of dentinal tissue, the main tissue of the tooth, is the subject of an increasingly comprehensive body of knowledge. The relationship between this microstructure and the mechanical behaviour of dentinal tissue remains, nonetheless, under question. This article proposes an original SEM analysis of dentin microstructure, accounting for lateral branches, and a mechanical model based on these findings. An interesting observation is that lateral branches have a dense collar, as do tubules. The diameter of these branches as well as a percentage area are quantified all along the depth of a dentin sample. We use these unprecedented data to build an orthotropic homogenized model of dentin. The heterogeneities of microstructure are taken into account using level-set functions. The results reveal that the lateral branches slightly influence the global homogenized elastic behavior of the dentin tissue, albeit creating stress concentration areas that are highly influenced by the inclination of the traction with respect to the tubule and branches. [Display omitted]